Performance of low cost sensor temperature logger in double jacket reactor vacuum distillation - Djoko Wahyudi; Wignyanto Wignyanto; Yusuf Hendrawan; Nurkholis Hamidi (Institute of Advanced Engineering and Science, 2024)
Heat transfer occurs due to the difference in temperature between the system and its surroundings. The effect of temperature can affect various aspects of the refining process, including efficiency, selectivity, reaction kinetics, and the quality of the final product. This study aims to analyze heat transfer in a double-jacket reactor by measuring temperature data taken using a temperature data logger system. Prototype low cost-effective temperature monitoring for double jacket reactor vacuum is this system integrates an Arduino Mega 2560, a type K thermocouple, amplifier MAX 6675 module, and an SD card data logger to measure and record reactor temperature for 30 minutes. The temperature data obtained is used to calculate the heat transfer and analyze the heat transfer characteristics of the reactor. Heat transfer analysis based on measured temperature data is able to provide insight into the characteristics of heat transfer in the observed system and can identify hot spots and heat transfer energy in the system. Thus, the temperature data logger used in the double jacket reactor in the vacuum distillation system can produce accurate data and information, and this system has broad application potential in temperature monitoring in various fields.